[TEX]\lim_{x \to 0} \frac{1-cos^3x}{3x^2}[/TEX]
[TEX]=\lim_{x \to 0} (\frac{1-cos^3x}{sin^2x} \frac{sin^2x}{3x^2}) (1)[/TEX]
Tính [TEX]\lim_{x \to 0} \frac{1-cos^3x}{sin^2x} (2)[/TEX]
Ta có : [TEX]1-cos^3x=1-cosx.cos^2x=1-cosx.(1-sin^2x)=1-cosx+cosx.sin^2x[/TEX]
[TEX]\frac{1-cos^3x}{sin^2x}=\frac{1-cosx+cosx.sin^2x}{sin^2x}=\frac{1-cosx}{sin^2x}+cosx[/TEX]
Mà [TEX]\frac{1-cos}{sin^2x}=\frac{2.sin^2\frac{x}{2}}{sin^2x}= \frac{1}{2.cos^2{\frac{x}{2}}}[/TEX]
Vậy, [TEX]lim (2) = \frac{1}{2}+1[/TEX]
Tính [TEX]\lim_{x \to 0} \frac{sin^2x}{3x^2}[/TEX]
Giới hạn này [TEX]=\frac{1}{3}[/TEX]
Vậy , [TEX]lim (1)=(\frac{1}{2}+1).\frac{1}{3}=\frac{1}{2}[/TEX]